Achieving Partial Nitritation by Treating Sludge With Free Nitrous Acid: The Potential Role of Quorum Sensing - Jiang, Cancan; Wang, Xu; Wang, Huacai; Xu, Shengjun; Zhang, Wei; Meng, Qingjie; Zhuang, Xuliang (Frontiers in Microbiology, 2022)
Partial nitritation is increasingly regarded as a promising biological nitrogen removal process owing to lower energy consumption and better nitrogen removal performance compared to the traditional nitrification process, especially for the treatment of low carbon wastewater. Regulating microbial community structure and function in sewage treatment systems, which are mainly determined by quorum sensing (QS), by free nitrous acid (FNA) to establish a partial nitritation process is an efficient and stable method. Plenty of research papers reported that QS systems ubiquitously existed in ammonia oxidizing bacteria (AOB) and nitrous acid oxidizing bacteria (NOB), and various novel nitrogen removal processes based on partial nitritation were successfully established using FNA. Although the probabilities that partial nitritation process might be achieved by the regulation of FNA on microbial community structure and function through the QS system were widely recognized and discussed, the potential role of QS in partial nitritation achievement by FNA and the regulation mechanism of FNA on QS system have not been reviewed. This article systematically reviewed the potential role of QS in the establishment of partial nitritation using FNA to regulate activated sludge flora based on the summary and analysis of the published literature for the first time, and future research directions were also proposed.